America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Romance revisited - Pearce, Lynne; Stacey, Jackie (New York University Press, 1995)
Après des décennies de féminisme et de déconstruction, la romance reste fermement ancrée comme une préoccupation centrale dans la vie de la plupart des femmes. Les taux de divorce montent en flèche, la famille traditionnelle est remise en question de toutes parts et pourtant la romance semble indestructible. En termes de représentation culturelle, la popularité de la romance semble également incontestée. La fiction populaire, le cinéma hollywoodien, les feuilletons télévisés et les médias en général affichent tous un appétit apparemment sans limite pour les sujets romantiques. Les pièges de la romance classique – mariages blancs, chansons d’amour, Saint-Valentin – sont plus que jamais commercialement viables. Dans cette anthologie d'essais originaux, la romance est revisitée sous un large éventail de perspectives, non seulement dans la fiction et le cinéma, mais dans toute une gamme de phénomènes culturels. Les essais couvrent des sujets tels que la Saint-Valentin, les relations interraciales, les visions érotiques médiévales et la fiction romantique moderne, la relation entre la poétesse lesbienne HD et Bryher, la blancheur omniprésente du désir romantique, l'érotisme lesbien à l'ère du SIDA et la romance publique de Charles et Diane.
Keywords: anthologie; approches et analyses; arts; classisme; discipline; histoire et politique; outils; ouvrages de références; patriarcat; racisme; romance; sexisme; sexualité; systèmes d'oppressions; thématiques; études culturelles; études littéraires